Etnografi Komunikasi Orang Tua - Anak di Kampung Inggris - Riza Al fakhuriziah; Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2016)
This research method used the study of communication ethnography with phenomenology approach. The result of the research stated that the communication pattern of parents and children in "Kampung Inggris" Dusun Mangunrejo Tulungrejo Village Pare Sub-district Kediri Regency was the primary communication process in using Ngoko Language that was dominated by Indonesian language. The child did not master and did not had the ability to use Javanese language well, in Java language level that exist in Javanese culture.